The Effect Of Serum StorageTime On Room Temperature On Creatinine And Uric Acid: Pengaruh Lama Penyimpanan Serum Pada Suhu Ruang Terhadap Kadar Kreatinin Dan Asam Urat - Lestari, Dzulia; Aliviameita, Andika (Medicra (Journal of Medical Laboratory Science/Technology), 2023)
The examination parameters used as a detection of impaired kidney function are ureum, creatinine, and uric acid. The purpose of this study was to determine the effect of serum storage duration at room temperature on creatinine and uric acid levels. The study was conducted by experimental method using 32 serum samples. The data obtained by one wayAnova statistical analysis on creatinine examination showed a significance value of p = 0.009 (p<0.05) meaning that there was an influence of the length of serum storage on creatinine levels at room temperature, while in uric acid levels showed a significance value of p = 0.047 (p<0.05) meaning that there was an influence of serum storage duration on uric acid levels at room temperature. The conclusions on the examination of creatinine and uric acid levels had a significant effect on the delay of the treatment group of 0 hours and 24 hours.